Insilico analysis on C2H2 zinc-finger interactions and effect of conservative substitution - M VIDHYA (International Journal of Pharma and Bio Sciences, 2017)
Zinc Finger protein motifs vary in structure and sequence among different superfamilies. They possess stable scaffold and perform highly specialized functions. These transcription factors are stable and rarely undergo conformational changes upon target binding.The multiple finger-like protrusions make tandem contacts with target molecules. The binding properties of these proteins depend on amino acid sequence of finger domains, the linker between fingers, higher order structure formed and the number of fingers making tandem contacts. They are highly versatile in modes of binding, even within the same class. They are found to bind to varying targets as DNA and other proteins.The study analyses variations exhibited in the binding of the C2H2 domain of the protein variant. Binding protein carrying conservatively substituted residues in place of target binding positions are studied. The differences in residues after conservative substitution were statistically differentiable, during clustering of atoms in the protein.